Correction to: Enhanced differentiation of human pluripotent stem cells into pancreatic progenitors co-expressing PDX1 and NKX6.1 - Bushra Memon (4792767) (2018)
Correction to: Enhanced differentiation of human pluripotent stem cells into pancreatic progenitors co-expressing PDX1 and NKX6.1 https://doi.org/10.1186/s13287-017-0759-z, published online 23 January 2018. The original article contains a number of small errors which the authors would like to clarify: 1)In Fig. 1a of the original article, FGF10 concentration should be 50 ng/ml – as correctly stated in the Methods section – instead of 100 μg/ml. 2)Also in Fig. 1a of the original article, Activin A and EGF concentrations should both be 100 ng/ml – as correctly stated in the Methods section – instead of 100 μg/ml. 3)In the Methods section under the sub-heading “Differentiation of human pluripotent stem cells into pancreatic progenitor”, the term, ‘50 ng/ml hFGF10’ should be omitted from the following sentence: “At the end of stage 3, media were changed to DMEM supplemented with 1% vol/vol B27, 0.25 mM vitamin C, 50 ng/ml hFGF10, 50 ng/ml hNOGGIN, 100 ng/ml hEGF, and 10 mM nicotinamide (Sigma, USA) for 4 days of stage 4 treatment for each protocol (Fig. 1a).” FGF10 was only added during stages 2 & 3 of differentiation as correctly depicted in Fig. 1a. The corrected version of Fig. 1a can be viewed ahead. The original article has been corrected. Other Information Published in: Stem Cell Research & Therapy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1186/s13287-018-1002-2